Cultures and Persons: Characterizing National and Other Types of Cultural Difference Can Also Aid Our Understanding and Prediction of Individual Variability - Smith, Peter Bevington; Bond, Michael Harris (Frontiers in Psychology, 2019)
Valid understanding of the relationship between cultures and persons requires an adequate conceptualization of the many contexts within which individuals work and live. These contexts include the more distal features of the individual’s birth ecology and ethno-national group history. These features converge more proximally upon individual experience as “process” variables, through the institutional-normative constraints and affordances encountered through socialization into a diverse set of cultural groupings. This enculturation is then revealed in the individual’s response profile of values, beliefs, choices, and behaviors at any given time. Cross-cultural psychologists have typically compared these encultured responses cross-nationally by averaging the scores of equivalent groups of persons across national groups, terming these average differences “cultural differences”. This procedure has generated considerable resistance, primarily due to careless over-generalization of results to all members of a given cultural group. Critics of nation-based characterizations have challenged their methodological and conceptual inadequacies, but we now know better how to address the measurement-related aspects of culture-level “psychological” variables, such as individualism-collectivism. In challenging the accuracy of these measures, critics have also neglected to acknowledge the continuing predictive and discriminant validity of these dimensions of national culture. We here review the utility of more recent measurements. We then show how nation-level comparisons can be used by psychologists to improve our understanding of individual, rather than group, outcomes. Nations are heterogeneous amalgams of ethnicities, social classes, organizations, school systems, and families. Individuals’ socialization into these groups affects their functioning at any given point in life. These enculturations are further dependent on their gender, age, and education. Assessment of culture’s relation with individual functioning requires adequate measurement of both personality and normative aspects of situations in which behavior is enacted. Once this integration of cultural influences is achieved, the logic and methodology for integrating national culture into psychological models of individual behavior can be applied within any nation where research focuses on how within-nation cultural variation affects individual functioning. Culture, conceptualized as normative group constraints, becomes more widely amenable to study, and the hard lessons learned from cross-national research can be used to guide the practice of more locally sensitive research.